2016
DOI: 10.1002/nme.5317
|View full text |Cite
|
Sign up to set email alerts
|

Field‐gradient partitioning for fracture and frictional contact in the material point method

Abstract: Contact and fracture in the material point method require grid-scale enrichment or partitioning of material into distinct velocity fields to allow for displacement or velocity discontinuities at a material interface. A new method is presented in which a kernel-based damage field is constructed from the particle data. The gradient of this field is used to dynamically repartition the material into contact pairs at each node. This approach avoids the need to construct and evolve explicit cracks or contact surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 63 publications
0
40
0
Order By: Relevance
“…It should be noted that compared to the standard finite element implementation, the implicit MPM does introduce additional computational costs, as a refactorization of the stiffness matrix introduced in Equation is required when material points move across background cells. However, this results in a high‐fidelity procedure for simulating complex phenomena (see, eg, previous studies) and also provides very accurate estimates for the crack geometry as will shown in Section 5. In this work, both the displacement field and the phase field that are defined at material points are mapped at the corresponding parent cell nodes resulting in an updated MPM Lagrangian phase.…”
Section: Numerical Implementationmentioning
confidence: 96%
See 1 more Smart Citation
“…It should be noted that compared to the standard finite element implementation, the implicit MPM does introduce additional computational costs, as a refactorization of the stiffness matrix introduced in Equation is required when material points move across background cells. However, this results in a high‐fidelity procedure for simulating complex phenomena (see, eg, previous studies) and also provides very accurate estimates for the crack geometry as will shown in Section 5. In this work, both the displacement field and the phase field that are defined at material points are mapped at the corresponding parent cell nodes resulting in an updated MPM Lagrangian phase.…”
Section: Numerical Implementationmentioning
confidence: 96%
“…More recently, cohesive modelling approaches have been introduced in an effort to further generalize the applicability of the MPM for problems pertinent to arbitrary crack paths . A continuum damage–based approach has been introduced in Homel and Herbold also demonstrating the advantages of using domain decomposition methods to accelerate MPM.…”
Section: Introductionmentioning
confidence: 99%
“…To this point, few research has been conducted in damage simulation utilizing MPM using either discrete [38,39], cohesive [40,41], or continuum damage models [42,43]. Taking advantage of the good qualities of phase field modelling in naturally resolving complex crack paths, a Phase Field Material Point Method According to Griffith's theory [47] the stored energy Ψ s of the body Ω can be expressed as…”
Section: Introductionmentioning
confidence: 99%
“…The CPDI improves the numerical accuracy of the MPM and prevents the occurrence of the nonphysical numerical fractures in the MPM, which is possible under the large extension condition. Given these advantages, the CPDI has been applied in the MPM simulations of, among others: nanoindentation, chemical/mechanical coupling of a silicon anode, the impact of thin‐walled structures as well as being enhanced to model fracture or fluid‐driven fracture . The CPDI has also been used in simulations of geotechnical problems, such as modeling pile penetration, pile installation, soil liquefaction, and the coupled analysis of saturated porous media …”
Section: Introductionmentioning
confidence: 99%